1992
DOI: 10.1128/jcm.30.4.757-763.1992
|View full text |Cite
|
Sign up to set email alerts
|

Survival of hepatitis A virus on human hands and its transfer on contact with animate and inanimate surfaces

Abstract: The survival of hepatitis A virus (HAV; strain HM175) on the hands of five volunteers was determined by depositing 10 ,ul of fecally suspended virus on each fingerpad and eluting the inoculum after 0, 20, 60, 120, 180, and 240 min. The amount of virus recovered from each fingerpad at 0 min was approximately 6.0 x 104 PFU. At the end of 4 h, 16 to 30%o of the initially recoverable virus remained detectable on the fingerpads. HAV inocula (10 ,ul; approximately 1.0 x 104 PFU) placed on fingerpads or 1-cm-diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
1
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(124 citation statements)
references
References 42 publications
6
114
1
3
Order By: Relevance
“…Many pathogenic viruses can remain viable on human hands for hours. 1,2 This gives hands the potential to spread such infectious agents directly or indirectly [3][4][5] in settings such as hospitals. 6,7 Recent studies with experimentally contaminated fingertips have further substantiated the potential of hands to spread viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Many pathogenic viruses can remain viable on human hands for hours. 1,2 This gives hands the potential to spread such infectious agents directly or indirectly [3][4][5] in settings such as hospitals. 6,7 Recent studies with experimentally contaminated fingertips have further substantiated the potential of hands to spread viruses.…”
Section: Introductionmentioning
confidence: 99%
“…The survival of HAV on hands and its transfer to hands or inanimate surfaces were studied by Mbithi et al (1992). They found that approximately 20% of the initial HAV inoculated on hands remained infectious for at least 4 hours, and that HAV inoculated onto a stainless steel surface survived for 2 hours.…”
Section: Hepatitis a Virus (Hav)mentioning
confidence: 99%
“…More recently, 1600 laboratory confirmed cases occurred in Czech Republic and 2800 in Latvia, during 2008 (Castkova & Benes, 2009;Perevoscikovs et al, 2009). HAV is also relatively resistant to many environmental conditions, physical and chemical agents (Mbithi, Springthorpe, Boulet, & Sattar, 1992), and may retain their infectivity for days to weeks in dried feces (McCaustland, Bond, Bradley, Ebert, & Maynard, 1982). Because of the absence of envelope the virus is very stable.…”
Section: Hepatits a (Hav)mentioning
confidence: 99%